Poor Yield of Routine Transthyretin Screening in Patients with Idiopathic Neuropathy. (4th November 2020) - Namiranian, Dina; Chalk, Colin; Massie, Rami
ABSTRACT: Background and objectives: Transthyretin familial amyloid polyneuropathy (TTR-FAP) is caused by a mutation in the transthyretin (TTR) gene. Although classically described as rapidly progressive and life-threatening, recent studies on TTR-FAP show significant genetic and phenotypic heterogeneity depending on geographic localization. In light of new therapeutic advances and their implication for patient management, the aim of our study was to determine the prevalence of TTR-FAP within patients with idiopathic neuropathy in a North American population. Methods: We sequenced the TTR gene in a cohort of patients with idiopathic neuropathy. Genetic screening was performed in 110 patients from two neuromuscular clinics in Montreal, Canada. Results: No variants of unknown significance or pathogenic mutations were detected in the TTR gene. Conclusion: Our study confirms that TTR-FAP is a rare entity in our patient population, and that diagnostic yield of screening all patients with idiopathic neuropathy is very low.